Self-Making through Self-Writing: Non-Sovereign Agency in Women's Memoirs from the Naxalite Movement - Lipika Kamra (South Asia Multidisciplinary Academic Journal)
Women were active participants in the Naxalite movement of the 1960s and 1970s in India but were made invisible in the mainstream historiography of the movement. However, memoirs and autobiographies of women Naxalites bring out their experiences of participation in the movement. This paper engages with the memoirs of two of them, K. Ajitha and Krishna Bandyopadhyay, and argues that these women demonstrate a non-sovereign agency in self-making through these autobiographical narratives.